The future of family farming: A literature review on innovative, sustainable and succession-oriented strategies. (October 2016) - Suess-Reyes, Julia; Fuetsch, Elena
Abstract: Family farms are exposed to severe economic, political, social and ecological changes. To enable intra-family succession and to safeguard the long-term survival of the farm, farming families are therefore increasingly forced to pursue market-driven, innovative and sustainable strategies. A multitude of different research areas has dedicated its research to the future of family farming and a synthesis of the existing literature on innovation, succession and sustainability in family farming seems timely and relevant. The purpose of this article is to systematically review and critically reflect on 53 articles addressing factors related to innovative, sustainable and succession-oriented strategies in family farming. As a theoretical framework, we apply the resource-based view. Findings indicate a strong fragmentation of approaches in all three topics making a cumulative progress of knowledge challenging. Furthermore, we notice a lack of theoretical references in the majority of articles reviewed. This implies the problem that the findings lack connectivity to each other which makes a scientific discourse between the different areas that contribute to research on family farms difficult. From a methodological point of view, research on family farms is rigorous. However, there is room for improvement when it comes to the development of theoretically grounded and empirically approved measurement scales. Furthermore, to stimulate multidisciplinary exchanges, we highlight recent developments in family business research with regard to innovation, sustainability and succession in family businesses and discuss their possible implications for research on family farms. Highlights: A state-of-the-art literature review on family farming is conducted. The reviewed topics include sustainability, succession and innovation. The heterogeneity of approaches complicates a cumulative knowledge progress. We transfer developments in family business research to research on family farms. Based on the current fragmentation, we call for a multidisciplinary dialogue.